Improve Student Learning Outcomes using Play Mode - Sejahtra Sejahtra (Universitas Majalengka, 2023)
The research objective was to achieve learning outcomes and improve student learning outcomes by using the playing method in the high jump physical education subject in Class V SD Negeri 065012 Medan in the 2022–2023 academic year. This type of research is called classroom action research, which is carried out in two cycles by following the steps of planning, implementing, observing, and reflecting. The research was conducted in Class V of SD Negeri 065012 Medan for the 2022–2023 academic year with 20 students. The data collection tool is in the form of a learning achievement test. The data analysis technique uses descriptive statistics by comparing the average value of cycles I and II. The results of the analysis of cycle I showed that 15 students (75%) completed and 5 students (25%) did not complete, with an average score of 70. The results obtained showed that cycle I was not completed in class because one class was declared classically completed if there were 85% of students in the class who completed the lesson. The results of the analysis of cycle II obtained 17 students (85%) who completed and 3 students (15%) who did not complete, with an average value of 75.5. The results obtained show that cycle II has been classically completed. Based on the results of data analysis, it can be concluded that students' learning outcomes are classically complete and improved by using the playing method in the High Jump Physical Education subject in class V SD Negeri 065012 Medan.